Surface water quality assessment based on GIS and hierarchical clustering technique: a case study of Cam Pha Region, Northeast Vietnam. (12th September 2019) - Vu, Danh Tuyen; Nguyen, Tien Thanh; Hoang, Anh Huy
This study is set out to assess surface water quality of three groups of chemical (pH, COD, NH4 + ), of physics (TSS) and of microorganisms (Coliform) in the Cam Pha mining area, northeast Vietnam. GIS and hierarchical clustering technique were used for interpolation and grouping samples that have similar water quality, respectively. The results showed that surface water quality was heavily contaminated. All of indicators do not meet Vietnam's National Technical Regulations (NTR), especially COD and TSS beyond NTR about ten times at many locations such as TSS at Ha Rang stream, NH4 + at Cau Four River and COD at Khe Sim stream. The worst and best water quality was detected at Ha Rang and Khe Sim and Lep My, Khe Re, and Ong Linh streams, respectively. The results of this study demonstrated GIS and hierarchical clustering technique are effective methods for surface water quality assessments.